A cultural theory and model of power relations. Issue 2 (4th May 2019) - Favre, Maroussia; Swedlow, Brendon; Verweij, Marco
ABSTRACT: Power is a central but frequently implicit and rarely modeled concept in political science. We integrate several diverse and seemingly incommensurate conceptions of power into a model classifying network ties between dyads along the dimensions of asymmetry and probability of compliance. We argue that this model mirrors the relational dimensions and patterns in Douglasian cultural theory (CT) and illustrate these varying configurations of power with examples from US presidencies. By integrating conflicting conceptions of power into a single theory-based and generalizable model, we seek to advance the study of power, networks, and culture.